Jorge Antunes : poética política e militância artística - Fernandes, Elina Padilha (2015)
This research deals with the production of the Brazilian composer and conductor Jorge Antunes (1942-), analyzing his musical poetics and the political gesture in two of his major works: Elegia Violeta para Monsenhor Romero (1980) and Sinfonia das Diretas (1984). Through these works it is possible to scale his political and artistic activism – during a historical moment in Brazil's military dictatorship (1964-1985) – and must disclose his innovative and experimental musical poetics.